Portable Pico Hydro Power Plant with Cross Flow Turbine by Water Springs Flow in Limau Manis Padang - Zulka Hendri; Yudia Meka Seftiani; Akbar Abadi; Wiwik Wiharti; Fandi Ahmad (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2024)
This research examines the design and implementation of a Portable Pico Hydro Power Plant (PHPP) featuring a cross-flow turbine with a capacity of 300 watts. Pico hydro is a compact and efficient form of hydropower generation tailored to meet the energy requirements of remote plantation areas. The primary aim of this study is to optimize the use of low-flow water sources and low-head conditions. The research encompasses a comprehensive evaluation of several critical factors, including the assessment of water source conditions, the selection of suitable turbine and generator designs, the configuration of the system, and a thorough performance evaluation. By employing a cross-flow turbine, the Pico Hydro system is designed to convert the kinetic energy generated by flowing water into mechanical energy, which is then transformed into electrical energy. The findings of this study reveal that the portable PHPP provides a stable and sustainable energy supply for off-grid locations. This system holds considerable promise for improving energy accessibility in rural and remote regions, positioning it as a viable solution for renewable energy applications.